2021
DOI: 10.3390/genes12020272
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Oxygenation in Inherited Diseases of the Retina

Abstract: (1) Background: The aim of our study was to investigate the relationship between retinal metabolic alterations (retinal vessel oximetry, RO) and structural findings (retinal vessel diameter, central retinal thickness and retinal nerve fiber layer thickness, RNFL) in patients with inherited retinal diseases (IRDs). (2) Methods: A total of 181 eyes of 92 subjects were examined: 121 eyes of 62 patients with IRDs were compared to 60 eyes of 30 healthy age-matched controls. The retinal vessel oximetry was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
2
5
0
Order By: Relevance
“…Furthermore, the present study shows that the retinal vessel diameters are affected in RP [ 22 , 23 , 24 ]. Consistent with the results of published studies [ 22 , 23 , 33 , 34 , 36 , 37 ], we found once again an increased A-SO 2 and even more, an increased V-SO 2 in in RP group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, the present study shows that the retinal vessel diameters are affected in RP [ 22 , 23 , 24 ]. Consistent with the results of published studies [ 22 , 23 , 33 , 34 , 36 , 37 ], we found once again an increased A-SO 2 and even more, an increased V-SO 2 in in RP group.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the results of previous studies [ 22 , 23 , 33 , 34 , 36 , 37 ] our RP patients showed again altered metabolic function by means of increased oxygen saturation of retinal arterioles and venules. Oxygenation of the human retina is a dynamic process, and regulation is necessary to provide a healthy metabolic environment [ 63 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Human retina metabolism is supported by oxygen supply, and abnormality in oxygen perfusion is linked to various ischemic and degenerative retinopathies, leading to visual impairment and blindness [99,100]. Oxygenation of the human retina is an energy-dependent process in which different mechanisms maintain the regulation [100].…”
Section: Oxygen Saturation Of the Maculamentioning
confidence: 99%
“… 6 10 Furthermore, there are reports of retinal oxygenation changes due to retinal vascular occlusions, 11 – 13 retinopathy of prematurity, 14 and inherited retinal degenerations. 15 , 16 Moreover, measurements of retinal oxygen saturation and metabolism have been reported in exudative age-related macular degeneration, 17 glaucoma, 12 , 18 20 and sickle cell retinopathy. 1 …”
Section: Introductionmentioning
confidence: 99%